Producing – Equipment, Methods and Materials - Factors Affecting the Rate of Deposition of Cement in Unfractured Perforations During Squeeze-Cementing Operations - G. W. Binkley; G. K. Dumbauld; R. E. Collins (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
A mathematical analysis has shown that the primary factors affecting the deposition of cement in unfractured perforations during squeeze-cementing operations are: the properties of the cement slurry, the geometry of the perforations, and the filtration time. The validity of the analysis has been substantiated by laboratory investigations. The information presented in this paper makes possible the prediction of the rate of deposition of cement in and about unfractured perforations under given squeeze-cementing conditions, the proper filtration time to control the amount of deposition to any desired value, and the deposition properties needed in cement slurries to restrict to any desired degree the formation of nodes of cement .Solids inside the casing. INTRODUCTION The deposition of solids against a permeable medium by the process of filtration is an important property of a cement slurry. General recognition of the role of filtration in the use of cement in wells is evident in view of the fact that several patents on low-water-loss cements have been issued during the past few years. In the conventional, high-pressure squeeze-cementing technique, a large volume of cement slurry is usually displaced into the area surrounding the perforated interval after the formation has been fractured hydraulically.' Near the end of the job, the pumping rate is slowed or stopped intermittently in an effort to obtain a high pressure in the wellbore. The way in which a high pressure is obtained is not understood thoroughly. but it is be- lieved to be caused by the deposition of a rigid mass of compacted cement particles either in the fractures of the formations or inside the casing opposite the perforated interval. In a method of squeeze-cementing introduced several years ago, a small amount of cement slurry is squeezed into the perforations at a low pressure to avoid fracturing the formation. The filling of the unfractured perforations with cement particles by the process of filtration is important to the success of this technique. Early in the development of this low-pressure squeeze-cementing technique, laboratory and field-size experiments showed that conventional, neat cement slurries were unsatisfactory if the tubing was extended into or through the perforated section of the casing. The extremely high filtration rate of neat cement slurries caused the deposition of a compacted mass of cement inside the casing and made it impossible to remove excess cement by reverse circulation and difficult to withdraw the tubing. Because the need for cements with a reduced filtration rate was obvioils and urgent, modified cements containing 12 per cent bentonite were used until research was completed on modified cements containing 25 per cent bentonite.< These modified cements were useful in the solution of the immediate problem, but the following questions remained unanswered: (I) what is the optimum filtration rate of cement slurries for this application, (2) how long should the squeeze pressure be applied. and (3) how great are the effects of squeeze pressure and well temperature on the rate of deposition? Furthermore, the relationship of the filtration properties of cement slurries to the dimensions of the perforations and the wellbore was unknown. In order to obtain information relative to these basic considerations, a systematic evaluation of all the factors involved in the deposition of Cement during low-pressure squeeze-cementing operations was initiated. Although the work was directed toward an evaluation of the factors influencing the deposition of Cement in the low-pressure squeeze-